2006
DOI: 10.1097/01.brs.0000244555.28310.40
|View full text |Cite
|
Sign up to set email alerts
|

Is Fusion Necessary for Surgically Treated Burst Fractures of the Thoracolumbar and Lumbar Spine?

Abstract: The short-term results of short segmental fixation without fusion for surgically treated burst fractures of the thoracolumbar spine were satisfactory. The advantages of instrumentation without fusion are the elimination of donor site complications, saving more motion segments, and reducing blood loss and operative time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
164
1
17

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(189 citation statements)
references
References 12 publications
7
164
1
17
Order By: Relevance
“…The results of this study are largely consistent with what has been reported in the literature, as well as previous studies by the investigators [6]. Good functional outcomes following posterior fixation for burst fractures without fusion have been reported in the literature, as measured by VAS, low-back outcome score, or the SF-36 [3,4].…”
Section: Commentarysupporting
confidence: 91%
See 1 more Smart Citation
“…The results of this study are largely consistent with what has been reported in the literature, as well as previous studies by the investigators [6]. Good functional outcomes following posterior fixation for burst fractures without fusion have been reported in the literature, as measured by VAS, low-back outcome score, or the SF-36 [3,4].…”
Section: Commentarysupporting
confidence: 91%
“…There have been several prospective trials comparing patients treated with posterior short segment instrumentation for thoracolumbar and lumbar burst fractures, randomized to fusion or no fusion, with largely similar outcomes [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of non fusion are several including elimination of donor site complications [22], sparing more motion segments, reduction of operative time during the surgery, of blood loss as well as reduced risks of infections, which is crucial in case of multi trauma or severely injured patients with multi organ posttraumatic failure syndrome [6].…”
Section: Mid-sagittal Index (Lines C)mentioning
confidence: 99%
“…Different authors who evaluated the loss of correction in the non fusion group (MISS) found no statistical evidence between the two groups (open vs. MISS) [6] and also stated that posterior fusion is unnecessary when managing patients with thoraco-lumbar burst fractures by short segment pedicle screw fixation [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation